Understanding Turkey's Syria policy during the Ak Party Era: from desecuritization to securitization - Gülbak, Okan (My University, 2018)
Bu tezin amacı, Güvenlikleştirme Teorisi çerçevesinde AK Parti Dönemindeki Türkiye’nin Suriye Politikasını incelemektir. Tezin temel argümanı, Türkiye’nin Güvenlik ve Dış Politika uygulamalarının birbirine sıkı sıkıya bağlı ve iç içe geçmiş olduğundan; güvenlikleştirme teorisinin, dramatik bir dönüşüm içinde olan Türkiye’nin Suriye Politikasını anlamakta en uygun analiz aracı olduğudur. Bu bağlamda çalışma, dönüşümün dinamiklerinin yalnızca geleneksel ve konstruktivist güvenlik yaklaşımlarının belli başlı temalarıyla anlaşılıp açıklanamayacağını tartışırken; aynı zamanda, bu yaklaşımları güvenliksizleştirme ve güvenlikleştirme teorisi ve bu teoriye gelen eleştiri ve katkılarla yeniden şekillendirilerek kapsayıcı bir yaklaşımla açıklamayı hedeflemektedir.

This thesis applied the securitization theory to the case of Turkey’s Syrian Policy during the AK Party era. The main argument was, because Turkey’s foreign and security policies were interconnected and intertwined with each other; the securitization theory was most suited analytical tool to understand the dramatic transformation in Turkey’s Syria Policy. Hence, the dynamics behind this transformation could not be understood only by using traditional or social constructivist approaches to the security. Rather, thesis aimed to develop an inclusive approach that combined the traditional and social constructivist approaches to security with the desecuritization and the securitization theory and also reframed them in the light of coming critics and contributions.
Keywords: AK Parti; AK Party; Desecuritization; Dış ilişkiler; Foreign relations; Güvenlikleştirme; Güvenliksizleştirme; Political Discourse; Politics and government; Siyasal Söylem; Siyaset ve yönetim; Suriye; Suriye Securitization; Syria; Turkey; Türkiye